NATURAL ZPT EFFECT ON GROWTH AND PRODUCTION OF SHALLOT (ALLIUM ASCALONICUM L) - Enny Mutryarny (SINTA Journal (Science, Technology, and Agricultural), 2020)
The purpose of this research is to know the influence of the natural ZPT to the growth and production of onion plants as well as to find out the best of 5 naturally tested treatments. Based on the research that has been carried out the results that the administration of ZPT naturally against the growth of red onions has a noticeable effect on the number of bulbs, fresh weight bulbs and dry weight bulbs. However, no real effect on the high observation parameters of plants and the number of leaves. Natural shallot treatment ZPT is best compared to 4 other treatments. Which gives the growth and production of the most excellent shallots